2020
DOI: 10.1055/s-0040-1713010
|View full text |Cite
|
Sign up to set email alerts
|

Women's Obstetric History and Midtrimester Cervical Length Measurements by 2D/3D and Doppler Ultrasound

Abstract: Objective The aim of the present study was to compare the obstetric history and both two- and tri-dimensional ultrasound parameters according to different cervical lengths. Methods The present cross-sectional study analyzed 248 midtrimester pregnant women according to cervical length and compared the data with the obstetric history and 2D/3D ultrasound parameters. Patients were divided into 3 groups according to cervical length: The Short Cervix group for cervical lengths ≥ 15 mm and < 25 mm (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 33 publications
(65 reference statements)
0
3
0
Order By: Relevance
“…Previous studies have already compared the straight technique with the curved technique [23], as well as the contribution of the volume of the uterine cervix for the diagnosis of short cervix. No technique showed better results compared to the standard technique [24][25][26][27][28][29].…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have already compared the straight technique with the curved technique [23], as well as the contribution of the volume of the uterine cervix for the diagnosis of short cervix. No technique showed better results compared to the standard technique [24][25][26][27][28][29].…”
Section: Plos Onementioning
confidence: 99%
“…In other words, the cervix becomes shorter but wider [23]. Although many studies have shown a correlation between cervical volume and the ability of this measure to contribute to the prediction of the risk of prematurity, none has demonstrated additional benefits in relation to the longitudinal cervical measurement technique [24][25][26][27][28].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation